Eritreja, moja dežela - Tomanić Trivundža, Ilija (Prispevki za novejšo zgodovino, 2022)
The article analyses how distant Others are represented in “Eritreja” photoreportage, that appeared in ten consecutive issues of the Mladina magazine between August and November 1988 and is regarded as the most extensive photoreportage ever published in Slovenian printed media. Multimodal framing analysis complemented with semi-structured interviews with the photographers are conducted to the examine verbal and visual strategies for the construction of Otherness. The divergence of this particular photoreportage from the leading news topics (famine and war) and its positive representations of the distant Other are traced to the photoreportage’s resonance with the domestic political agenda (Slovenia’s struggle against the centralisation of Yugoslavia) and Mladina’s editorial policy (advocating freedom of speech via challenging taboo topics in Yugoslavia).
Keywords: Etiopija; komunikacijska neenakost; Novinarska fotografija; okvirjanje; reprezentacija drugega; Socializem